Application of Different Biosensors for Cancer Detection - Chen, Xueyan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cancer is one of the main causes of death for humans while early detection can greatly lower cancer mortality and save lives. Therefore, reliable, cost-effective, and powerful technologies to detect the disease are needed. Cancer biomarkers are substances such as nucleic acids, enzymes, and metabolites, present in cancer clusters, tumours, or serum. While biosensors provide a quick, accurate, sensitive, uncomplicated, and economical method of diagnosing a particular cancer biomarker and is important to cancer detection and treatment, especially early diagnosis. Biosensors could be classified into three types: mass-based, electrochemical, or optical biosensors. With the development of science and technology and continuous research, more biosensors are designed for advanced technology, such as nanotechnology. The new and novel biosensors provide a powerful way for cancer detection. The objective of this research is to discuss the novel biosensors designed in recent years. In the future, more powerful biosensors will be designed and applied to cancer diagnosis and treatment.